2018
DOI: 10.1093/arclin/acy006
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Sustaining a Sport-related Concussion: An Initial Synthesis Study of 12,320 Student-Athletes

Abstract: An initial aggregate model of weighted bio-cognitive factors associated with increased odds of sustaining a SRC was developed. Previously validated factors were confirmed, yet a large source of variance remained unexplained. These findings emphasize the need to expand the host factors studied when assessing SRC risk, and that the existing, empirically based bio-cognitive factors do not adequately quantify the risk of SRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 46 publications
3
32
1
Order By: Relevance
“…Prior work has consistently demonstrated that individuals with previous concussions are at increased risk to sustain a future concussion. [7][8][9][10][11] Our present findings are consistent in magnitude with the majority of these findings (~2-3 times higher risk of future sports-related concussion with any prior history of concussion). However, in contrast to prior work, history of concussion was not retained in multivariate models in this sample.…”
Section: Sports-related Concussion Risk Factorssupporting
confidence: 89%
See 2 more Smart Citations
“…Prior work has consistently demonstrated that individuals with previous concussions are at increased risk to sustain a future concussion. [7][8][9][10][11] Our present findings are consistent in magnitude with the majority of these findings (~2-3 times higher risk of future sports-related concussion with any prior history of concussion). However, in contrast to prior work, history of concussion was not retained in multivariate models in this sample.…”
Section: Sports-related Concussion Risk Factorssupporting
confidence: 89%
“…Prior research indicates that the risk of sustaining a sports-related concussion is anywhere from 1.75 to 11 times greater for those with a history of one or more prior concussions. [7][8][9][10][11] In one of the largest retrospective studies to date (n = 12,320 participants), the odds of sustaining a sports-related concussion was 10.65 times greater than for those with a history than those without. 8 Therefore, while the specific magnitude of this effect is not necessarily clear, it is apparent that prior sports-related concussion is a predisposing factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…48,49 We also examined risk factors for football-related concussion in this sample of youth athletes, finding that both history of prior concussion and history of depression were associated with greater risk for incident concussion. History of prior concussion has been reported as a risk factor for concussion in multiple prior studies, [23][24][25][26] likely owing to its function as a marker of risk. In other words, a prior history of concussion suggests a greater propensity to concussion, whether owing to genetic factors or environmental exposure (such as style of play or position).…”
Section: Discussionmentioning
confidence: 99%
“…Most research on comorbid conditions in relation to concussion outcome has focused on depression and anxiety [14,35,37,[41][42][43][44]. More and more work has shown a link between behavioural disorders (such as ADHD) and learning disabilities as contributing factors to concussion symptom and severity presentation [45][46][47][48]. As an example, participants with ADHD were significantly more disabled after suffering a concussion than were control participants without ADHD, even when controlling for age and sex [49][50][51][52][53].…”
Section: Agementioning
confidence: 99%